Sistem Penunjang Keputusan Untuk Menentukan Rangking Taraf Hidup Masyarakat Dengan Metode Simple Additive Weighting - Daniel Rudiaman Sijabat, Anita , (PROCEEDING IC-ITECHS 2014, 2014)
Poverty  is  a  global  problem  that  is  experienced  by  many  developing  countries,including Indonesia. One thing that has been done to overcome poverty is the provision of direct assistance to people living below the poverty line. However, the provision of assistance to the poor people are often not well targeted, because the data is inaccurate or not up to date. Another cause is the number of criteria that must be evaluated for the determination of poor people who deserve to get help. Use of Simple Additive Weighting (SAW) can facilitate the determination of the poor based on the criteria specified. SAW is one method used to solve the problem that  has  many  attributes  (Multiple Attribute Decision  Making).  In this  study  we developed a SAW-based Decision Support System that can assist in determining the eligible poor people to get help. With the help of this system, the distribution of   aid will be better targeted.